THE CAPABILITY OF INFORMATION COMMUNICATION TECHNOLOGY TO BOOST INDONESIA ECONOMIC GROWTH: STUDY FROM 34 PROVINCES - Muhammad Dzaky Roshif Prasetyo; Ariska Nurfajar Rini (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2022)
The Information Communication Technology (ICT) development in Indonesia is in line with the development of ICT globally. The development of ICT has major challenges because there are still gaps, both in terms of users and signal. Technology and education are one of the determining factors that affect economic growth. However, inequality occurs not only in ICT but also in education. Based on the phenomena, this study aims to examine the impact of ICT users, ICT signal, and education on economic growth in 34 provinces in Indonesia for the 2015-2020 period. Data analysis uses the Fixed-Effect Model with secondary data in the form of panel data from 2015-2020. The results show that all ICT variables have a positive and significant effect on Indonesia's economic growth, except for the variable, fixed line telephone users and education have a negative effect on Indonesia's economic growth. This different findings may due to the heterogeneous characteristics of the provinces in our sample.